The economic burden of HIV/AIDS on individuals and households in Nepal: a quantitative study. Issue 1 (December 2017) - Poudel, Ak; Newlands, David; Simkhada, Padam
Abstract Background There have been only limited studies assessing the economic burden of HIV/AIDS in terms of direct costs, and there has been no published study related to productivity costs in Nepal. Therefore, this study explores in detail the economic burden of HIV/AIDS, including direct costs and productivity costs. This paper focuses on the direct costs of seeking treatment, productivity costs, and related factors affecting direct costs, and productivity costs. Methods This study was a cross-sectional, quantitative study. The primary data were collected through a structured face-to-face survey from 415 people living with HIV/AIDS (PLHIV). The study was conducted in six representative treatment centres of six districts of Nepal. The data analysis regarding the economic burden (direct costs and productivity costs) was performed from the household's perspective. Descriptive statistics have been used, and regression analyses were applied to examine the extent, nature and determinants of the burden of the disease, and its correlations. Results Average total costs due to HIV/AIDS (the sum of average total direct and average productivity costs before adjustment for coping strategies) were Nepalese Rupees (NRs) 2233 per month (US 30.2/month), which was 28.5% of the sample households' average monthly income. The average total direct costs for seeking HIV/AIDS treatment were NRs 1512 (US 20.4), and average productivity costs (before adjustment for coping strategies) were NRs 721 (US 9.7). The average monthly productivity losses (before adjustment for coping strategies) were 5.05 days per person. The major determinants for the direct costs were household income, occupation, health status of respondents, respondents accompanied or not, and study district. Health status of respondents, ethnicity, sexual orientation and study district were important determinants for productivity costs. Conclusions The study concluded that HIV/AIDS has caused a significant economic burden for PLHIV and their families in Nepal. The study has a number of policy implications for different stakeholders. Provision of social support and income generating programmes to HIV-affected individuals and their families, and decentralising treatment services in each district seem to be viable solutions to reduce the economic burden of HIV-affected individuals and households.